Ensino de discriminação de acordes baseado em treino de abstração e formação de classes de equivalência - Reis, Luis Fernando Toniollo (Universidade Federal de São Carlos, 2011)
The present study aimed to perform a music perception training for musically untrained individuals. Four university students were asked to identify major, minor and seventh chords. After hearing the sounds, they were reinforced for choosing the right image, which were either the chords guitar charts or the words MAIOR , MENOR and SÉTIMA (major, minor and seventh in Portuguese). After the training, the relation between words and charts was tested, and then, a generalization test took place in order to verify the identification of unheard chords. After this test, a new training was conducted with chords from a different root note. New equivalence tests were added, involving the different charts trained. Then, there a new generalization test was carried out, followed by the last training phase and the last testing phase. The participants generalized the trained discriminations to untrained stimuli, with an increasing score as they advanced through the procedure. However, some participants weren t able to achieve the criterion score in the more complex training sessions. These participants performed the equivalence tests, and their score was significantly lower than expected, failing to replicate prior results, and suggesting a link between difficulty in training and equivalence classes formation.
Keywords: Psicologia experimental; Abstração; Discriminação auditiva; Equivalência de estímulos; Acordes; Generalização; Abstração; Educação musical; Abstraction; CIENCIAS HUMANAS::PSICOLOGIA